Analysis of the relationship between field size and change in radiation dose to patient and staff based on radiographic technique in fluoroscopy and radiography - Karin Cristiane Ferreira; Valeriy Denyak; Maria Cristina de Alencar Nunes; Gracielly Soares Nunes; Jessica Villa Real; Danielle Filipov (Brazilian Journal of Radiation Sciences, 2024)
In discussions of radiological protection issues in fluoroscopy and radiography the radiation field size is usually mentioned in connection with unnecessary irradiation of the patient’s body parts that do not need to be imaged. However, excessive expansion of the field size leads also to some other effects: the excessive irradiation of assistants and visualized part of patient's body as well as the change in dose rate at the entrance of patient’s body by automatic brightness control. The aim of the present paper is to describe the results of an experimental study of the dependence of such effects on irradiation field size and primary X-ray spectrum. The measurements were carried out in conditions close to those of barium meal test. To simulate the patient body, 5 acrylic plates measuring 30 cm high x 30 cm long x 3 cm thick each were used, totalling 15 cm thick. The X2 RF Sensor (RAYSAFE) was used to measure the dose rate at the entrance and exit surface of the simulator and the specific model for measuring leakage and dispersion, the X2 Survey sensor (RAYSAFE), was used to measure the occupational dose rate. The occupational dose rate detector was located at the position that assistant usually maintains to support the patient's head and/or to administer the contrast. The results show that in radiographic mode dose rate at the exit of the patient’s body increases with the increase of field size. This increase reaches 85%. The increase of occupational dose rate in radiographic mode reaches 850% and is linearly proportional to the field area. In fluoroscopic mode, dose rate at the entrance of the patient’s body decreases proportionally to the increase of field side length because of the automatic brightness control. This effect reaches 25% with grid and 50% without grid.